НЕКОТОРЫЕ ИТОГИ РАБОТЫ ТЕРАПЕВТИЧЕСКОЙ СЛУЖБЫ СТАВРОПОЛЬСКОГО КРАЯ ЗА 2012 ГОД - Е. В. Кубышкина; Н. А. Рубанова (SINAPS LLC, 2013)
The most numerous, branched and closer to the population is therapeutic service of the Stavropol territory. In the structure of doctors of all specialities of physicians, therapists make up about 10 percent. Therapeutic service is constantly being improved, the priority becomes prophylactic direction. This article presents some results of work of therapeutic service of the Stavropol territory in recent years.